Avaliação do perfil de consumo de Gás Natural Veicular no estado do Amazonas em comparação com o consumo nacional - Said, Paloma Costa (Universidade Federal do Amazonas, 2018)
In Amazonas, the growth in the distribution and commercialization of Natural Gas is mainly linked to its use in industries and thermoelectric plants, causing a desire of Natural Gas to be used in automotive vehicles. In this work there is the comparative analysis of the percentage of consumption of Natural Gas in relation to other opitions. In Brazil, the consumption of VNG is more concentrated in the southern region of the country, leaving the northern region with the lowest index. There are four types of fuels marketed in Brazilian service stations; Gasoline, Ethanol, Diesel and the least used, Vehicular Natural Gas (VNG). For this reason, greater investments are of importance to encourage the use of this energy as an alternative fuel. With its distribution and commercialization it will generate employment and income for the population, leading to a more balanced environment, especially with regard to the Amazon.According to Lobkov; "Air quality and hence population health are very vulnerable to pollutants emitted by vehicles, and those driven by diesel have a large share in such emissions. Therefore, in the case of alternative fuels, it is extremely important to know in detail the impacts of replacing a more polluting fuel, diesel, with theoretically less polluting fuels such as natural gas."